Disguised Autobiography as Clinical Case Study. Issue 6 (2nd November 2019) - Bromberg, Chaim E.; Aron, Lewis
Abstract : Since the earliest days of psychoanalytic scholarship, observations gained from self-analysis or from the author's own psychoanalytic treatment have often been disguised as data obtained from clinical practice with patients. Some significant portion of our intellectual history originates in the analysis or self-analysis of analysts themselves, and this paper assumes the task of reviewing a collection of known or suspected autobiographical accounts and the associated theoretical developments and clinical concepts that can be traced back to these works. Though not a comprehensive survey, we begin with Sigmund Freud's discovery of screen memories through self-analysis and discuss examples including Anna Freud, Wilhelm Stekel, Melanie Klein, Sándor Ferenczi, Heinz Kohut, and others.